Hyper-N-glycosylated SAMD14 and neurabin-I as driver autoantigens of primary central nervous system lymphoma - Thurner, Lorenz; Preuss, Klaus Dieter; Bewarder, Moritz; Kemele, Maria; Fadle, Natalie; Regitz, Evi; Altmeyer, Sarah; Schormann, Claudia; Poeschel, Viola; Ziepert, Marita; Walter, Silke; Roth, Patrick; et al. (Blood, 2018)
To address the role of chronic antigenic stimulation in primary central nervous system lymphoma (PCNSL), we searched for autoantigens and identified sterile α-motif domain containing protein 14 (SAMD14) and neural tissue-specific F-actin binding protein I (neurabin-I) as autoantigenic targets of the B-cell receptors (BCRs) from 8/12 PCNSLs. In the respective cases, SAMD14 and neurabin-I were atypically hyper-N-glycosylated (SAMD14 at ASN339 and neurabin-I at ASN1277), explaining their autoimmunogenicity. SAMD14 and neurabin-I induced BCR pathway activation and proliferation of aggressive lymphoma cell lines transfected with SAMD14- and neurabin-I-reactive BCRs. Moreover, the BCR binding epitope of neurabin-I conjugated to truncated Pseudomonas exotoxin-killed lymphoma cells expressing the respective BCRs. These results support the role of chronic antigenic stimulation by posttranslationally modified central nervous system (CNS) driver autoantigens in the pathogenesis of PCNSL, serve as an explanation for their CNS tropism, and provide the basis for a novel specific treatment approach.
EVALuna2:35098